SOME CONSTRAINTS IN ACHIEVING SCIENCE PROCESS SKILLS (SPS) IN SECONDARY SCHOOL WATULIMO DURING THE COVID-19 PANDEMIC - Ericha Ayusepta Marviyani; Erman Erman (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This study aims to determine the constraints of the achievement of learning Science Process Skills (SPS) in the Covid-19 pandemic. This research used case study method with the research subject 5 science teacher and 15 students from 3 junior high school in Watulimo. The research instrument consisted of a questionnaire of teachers and students, with data collection techniques used were interviews, observation and documentation. The results of the research show that there are constraints derived from internal factors and external factors of the students. In addition there are also constraints that come from the teacher. Some of these constraints affect the low SPS students. Solution for the application of science process skills can be maximally implemented including, 1) the teacher should develop instruments such special student worksheet for assessing science process skills; 2) teachers need to familiarize the application of science process skills in science learning. The results of this study are used as input or solutions for junior high school science teacher against any problems that arise in SPS learning when the learning is online so that students are able to achieve the learning outcomes to the fullest.